Halomonas Rhizobacteria of Avicennia marina of Indian Sundarbans Promote Rice Growth Under Saline and Heavy Metal Stresses Through Exopolysaccharide Production - Mukherjee, Pritam; Mitra, Abhijit; Roy, Madhumita (Frontiers in Microbiology, 2019)
The Halomonas species isolated from the rhizosphere of the true mangrove Avicennia marina of Indian Sundarbans showed enhanced rice growth promotion under combined stress of salt and arsenic in pot assay. Interestingly, under abiotic stress conditions, Halomonas sp. Exo1 was observed as an efficient producer of exopolysaccharide. The study revealed that salt triggered exopolysaccharide production, which in turn, increased osmotic tolerance of the strain. Again, like salt, presence of arsenic also caused increased exopolysaccharide production that in turn sequestered arsenic showing a positive feedback mechanism. To understand the role of exopolysaccharide in salt and arsenic biosorption, purified exopolysaccharide mediated salt and arsenic sequestration were studied both under in vivo and in vitro conditions and the substrate binding properties were characterized through FT-IR and SEM-EDX analyses. Finally, observation of enhanced plant growth in pot assay in the presence of the strain and pure exopolysaccharide separately, confirmed direct role of exopolysaccharide in plant growth promotion.